Zero emission heating with calcium oxide and water: development and demonstration of first pilot scale thermochemical heating system for buildings - Schmidt, Matthias; Sourmelis, Venizelos; Kühl, Viktor; Linder, Marc (Frontiers in Energy Research, 2025)
Heat supply for residential buildings is still mainly based on fossil fuels and is thus a significant contributor to CO2 emissions. Renewable heating remains a technological challenge, often for the reason that during cold weather periods heat demand increases drastically whereas renewable production minimizes. Reactive solids produced by renewable energy can be an energy storage and carrier to flexibly leverage the often extreme seasonal discrepancy of residential heat demand. This work demonstrates a fully integrated thermochemical heating system based on calcium oxide and water operational for the first time in a real building environment. With the extraction of the thermochemically stored energy at a temperature level of 60°C we proved that the technology can be integrated into existing heating infrastructures of buildings, by replacing fossil fuel-based burners. This work advances the technology readiness level of thermochemical energy storage to validation in relevant environment.